Endocytotic Pathways in Human Adipose Stem Cells and Their Regulation by Intracellular Calcium Oscillations and the Neonatal Fc Receptor - Morshed, Md Tanvir; Justus Liebig University Giessen (My University, 2025)
Intracellular calcium (Ca2+) oscillations in human adipose stem cells (hASCs) act as a regulatory switch for absorbing albumin and recycling IgG. By using various chemical blockers, genetic knockdown (siRNA), and the anti neonatal Fc receptor (FcRn) antibody nipocalimab, this study demonstrated that the presence of albumin or IgG triggers these Ca2+ signals via the FcRn. In turn, these Ca2+ oscillations drive the cells to internalize albumin through three distinct cellular entry pathways—macropinocytosis, caveolae-dependent, and clathrin-mediated endocytosis—establishing a tight feedback loop where FcRn and Ca2+ signaling mutually control nutrient and antibody processing in hASCs.
Keywords: Endocytosis; Neonatal Fc Receptor; Immunoglobulin G; Albumin; Calcium; Human Adipose Tissue derived stem cell; ddc:610